Productive performance of Brown Swiss cattle in peruvian high plains - Quispe Coaquira, Jesús (2016)
The study determined the effects of year and season of birth and sex or parturition on body weight and gain body and milk production of Brown Swiss cattle. It was used records from productive events of 2003-2010; the data are analyzed in factorial arrangements relevant and conducted in Randomized Complete Design. The average birth weight was 46.35 ± 7.01 kg, with differences to year and season of birth and sex factors (P = 0.05). Weight at year reached 252.37 ± 27.11 kg and gains to 180 days and one year of age were 103.68 ± 11.74 and 207.25 ± 27.61 kg, respectively; there were no differences for the factors. During the ﬁrst year, recording the live weight showed linear and growing trend. Milk production has varied from 2911.96 to 3551.77 kg (P = 0.05); also they showed variations per year and season of calving and lactation number. Real milk production varied considerably (from 2881.96 to 3695.32 kg) and the lactation period of 301.29 to 341.28 days both variables were different (P = 0.05) for calving season and lactation number. The lactation curve was different to year and season of calving and lactation number; there was no expression of the lactation peak in any case Production levels achieved, in meat and milk, are within the parameters reported at the level of the region and the milk watershed of the country.